Upaya Meningkatkan Kemampuan Berfikir Logis Matematis Mahasiswa Papua Dalam Pemecahan Masalah Luas Daerah Di Bawah Kurva Normal - Wiyanti, Wiwik (Pendidikan Matematika Universitas PGRI Yogyakarta, 2017)
To improve the logical thinking ability of Papuan students, this research was conducted. The material subject of this research is how to solve the wide of the area under the normal curve. The subject of the research is Papuan students in Class of Statistika Dasar in Mathematics Education major in STKIP Surya Tangerang 2016/2017 academic year. The methods of this research are Qualitative. Data had collected with Test and interview and to data analysis was using Descriptive Qualitative. The design of this research used Action Research. The result showed that 1) Students with the high math problem-solving skill the area under the normal curve have been able to think coherently, as well as could completion of the work in consecutively and correctly. 2) Students with the math problem-solving ability, have been able to think coherently already did the problem in order, but still make errors in final calculation, because careless. 3) Students with low ability in math problem solving, have been able to think coherently already do the problem in order, but there was still a lot of mistake calculations in basic calculations like a division of integer, and as well as the final calculations. Kata Kunci: action, logical, thinking, curve, normal